Approaches to messenger RNA detection - comparison of methods - Dvořák, Zdeněk; Pascussi, Jean-Marc; Modrianský, Martin (Biomedical papers, 2003)
Detection of messenger RNA is an important part of current biomedical research, although utilized for decades. This communication endeavors to compare three most commonly used techniques of mRNA detection, i.e. Northern blot, ribonuclease protection assay (RPA), and real-time polymerase chain reaction (RT-PCR). Principles and general procedures of these methods are described, and advantages and weaknesses of each are discussed in terms of their specificity, sensitivity, difficulty, time and material demands as well as health and environmental risks. We conclude that choice of any method discussed depends on particular purpose, experience of the researcher, and on laboratory equipment and organization.
Keywords: Messenger RNA / Northern blot / Ribonuclease protection assay / Real time polymerase chain reaction